2021
DOI: 10.1371/journal.pntd.0008736
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for zoonotic transmission of malaria in the Atlantic Forest: Exploring the effects of variations in vector abundance and acrodendrophily

Abstract: Transmission foci of autochthonous malaria caused by Plasmodium vivax-like parasites have frequently been reported in the Atlantic Forest in Southeastern and Southern Brazil. Evidence suggests that malaria is a zoonosis in these areas as human infections by simian Plasmodium species have been detected, and the main vector of malaria in the Atlantic Forest, Anopheles (Kerteszia) cruzii, can blood feed on human and simian hosts. In view of the lack of models that seek to predict the dynamics of zoonotic transmis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Further support for the zoonotic malaria hypothesis is the biting behavior of An . cruzii in the canopy where non-human primates forage and on the ground level where humans walk inside forest ( Medeiros-Sousa et al., 2021 ). The origin of zoonotic malaria caused by P .…”
Section: Introductionmentioning
confidence: 99%
“…Further support for the zoonotic malaria hypothesis is the biting behavior of An . cruzii in the canopy where non-human primates forage and on the ground level where humans walk inside forest ( Medeiros-Sousa et al., 2021 ). The origin of zoonotic malaria caused by P .…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models for the COVID-19 pandemic have been proposed to assess the effectiveness of NPIs and study the dynamic behavior of the pandemic ( Medeiros-Sousa et al, 2021 , Zhou et al, 2020a , Wu et al, 2020 , Britton et al, 2020 , Chang et al, 2021 ). Recently reported models have utilized human mobility to predict the number of new confirmed cases under various NPI scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Kerteszia females are opportunistic and can seek non-human primates, birds, and other animals in the canopy as well as humans and other mammals at ground level [16]. Mathematical modeling has shown that simian malaria transmission to humans is more likely to occur at forest edges, where vector displacement from the canopy is greater, simian species are present, and biodiversity effects that regulate vector abundance are lower [17].…”
Section: Introductionmentioning
confidence: 99%